2016
DOI: 10.1002/mnfr.201501019
|View full text |Cite
|
Sign up to set email alerts
|

N‐methylnicotinamide protects against endothelial dysfunction and attenuates atherogenesis in apolipoprotein E‐deficient mice

Abstract: The present study reveals a novel mechanism through which MNA improves endothelial dysfunction and attenuates atherogenesis via the modulation of ADMA-DDAH axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Third, plasma NAM concentrations were not determined at the beginning of the experiment; however, genetically identical untreated ApoE-deficient mice had significantly lower plasma concentrations of NAM than NAM-treated mice. Fourth, me-NAM, a metabolic product of NAM [ 54 ], is also atheroprotective [ 76 , 77 ]. Thus, by increasing the plasma concentration of me-NAM, NAM administration might also contribute to preventing atherosclerosis development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Third, plasma NAM concentrations were not determined at the beginning of the experiment; however, genetically identical untreated ApoE-deficient mice had significantly lower plasma concentrations of NAM than NAM-treated mice. Fourth, me-NAM, a metabolic product of NAM [ 54 ], is also atheroprotective [ 76 , 77 ]. Thus, by increasing the plasma concentration of me-NAM, NAM administration might also contribute to preventing atherosclerosis development in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme catalyses the methylation of nicotinamide (NA) with the use of S‐adenosyl‐methionine (SAM) as a methyl group donor, thus reduces an availability of NA as a substrate for NAD + synthesis and decreases SAM content. It was also suggested that the final product of NNMT activity that is methyl‐nicotinamide (MNA) may directly regulate inflammatory processes and influence eNOS activity in endothelial cells (Bar et al, 2017; Jiang et al, 2016). Therefore, a putative role of NNMT as an important regulatory enzyme involved in a proper endothelial functioning has been considered, and it was a reasonable justification of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they showed that both of MNAM and perindopril activate ACE2/Ang-(1-7) and inhibit the ACE/Ang II axes and vasoprotective effects of MNAM were similar to perindopril (Bar et al, 2017). In addition, (Jiang et al, 2016) ADMA metabolizer-and thereby reduces ADMA levels and increases NO availability (Jiang et al, 2016).…”
Section: Figurementioning
confidence: 97%
“…Furthermore, they showed that both of MNAM and perindopril activate ACE2/Ang‐(1–7) and inhibit the ACE/Ang II axes and vasoprotective effects of MNAM were similar to perindopril (Bar et al, ). In addition, (Jiang et al, ) reported possible mechanism underlying the effects of MNAM on the regulation of ADMA levels. They indicated that MNAM probably controls methylation state of DDAM (dimethylarginine dimethylaminohydrolase)—a ADMA metabolizer—and thereby reduces ADMA levels and increases NO availability (Jiang et al, ).…”
Section: Mnam and Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation